Numerical Research and Parametric Study on the Thermal Performance of a Vertical Earth-to-Air Heat Exchanger System. (23rd July 2021) - Zhang, Zhening; Sun, Jindong; Zhang, Zhenxing; Jia, Xinxin; Liu, Yang
Abstract : The earth-to-air heat exchanger (EAHE) system, as a clean and efficient shallow geothermal energy application technology, has obvious effects in reducing the energy consumption of passive low-energy buildings. The traditional horizontal EAHE system is difficult to apply and popularize due to its large occupation, unfavorable shallow soil temperature, and difficulty in timely centralized discharge of condensed water. This paper proposes a new type of vertical earth-to-air heat exchanger (VEAHE) system. The VEAHE system has a number of advantages such as smaller occupation, efficient geothermal energy utilization, and centralized discharge of condensed water. In order to evaluate the influence of different parameters on the thermal performance of the VEAHE system, a mathematical model of the VEAHE system was developed. And, the data calculated by the model highly tallied with the experimental data. The results showed that laying thermal insulation layers at the outlet of risers will effectively restrain the interference of downcomers to risers. It is advisable to set thickness and length of the insulation layer at 30 mm and 3 m. Considering the compromise between thermal performance and construction costs of the VEAHE system, the length of the ducts at 30–50 m and the diameter at 150–250 mm are recommended. The air supply volume of a single shaft can reach 500–1200 m 3 /h as the air velocity reaches 3–7 m/s.